2014
DOI: 10.1177/1457496914520854
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the development of early osteoarthritis following lateral tibial plateau fractures: mid-term clinical and radiographic outcomes of 73 operatively treated patients

Abstract: The postoperative articular congruity and normal mechanical axis of the lower leg after plate fixation in lateral tibial plateau fractures seem to have a role in prevention of posttraumatic osteoarthritis but does not appear to predict clinical outcome at medium-term follow-up. The role of initial dislocation and associated cartilage damage in the development of osteoarthritis following these fractures is still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 34 publications
4
58
1
6
Order By: Relevance
“…In literature, this complication has been reported between 0% and 59% 25, 26, 27. The large variation in reporting could be due to different criteria used for evaluation, reliability of techniques used for measuring and quality of radiographs used for the purpose of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, this complication has been reported between 0% and 59% 25, 26, 27. The large variation in reporting could be due to different criteria used for evaluation, reliability of techniques used for measuring and quality of radiographs used for the purpose of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…, 19 In addition to all initial articular cartilage damage was accused for the development of arthritis 20 …”
Section: Discussionmentioning
confidence: 99%
“…Blokker et al suggested surgical treatment when the articular surface depression was > 5 mm (8). Reduction of the articular surface by plate and screws can also reduce the risk of degenerative changes of the knee (24). …”
Section: Discussionmentioning
confidence: 99%